HP Nonstop server security a practical handbook - Hill, Terri; Alvarado, Ellen; XYPRO Technology Corporation (Amsterdam ; Boston : Elsevier Digital Press, 2004)
Since the last publication of the Ernst and Young book on Tandem security in the early 90's, there has been no such book on the subject. We've taken on the task of supplying a new Handbook whose content provides current, generic information about securing HP NonStop servers. Emphasis is placed on explaining security risks and best practices relevant to NonStop environments, and how to deploy native security tools (Guardian and Safeguard). All third party vendors who supply security solutions relevant to NonStop servers are listed, along with contact information for each vendor. The Handbook is a source for critical information to NonStop professionals and NonStop security administrators in particular. However, it is written in such a way as to also be extremely useful to readers new to the NonStop platform and to information security. This handbook familiarizes auditors and those responsible for security configuration and monitoring with the aspects of the HP NonStop server operating system that make the NonStop Server unique, the security risks these aspects create, and the best ways to mitigate these risks. Addresses the lack of security standards for the NonStop server Provides information robust enough to train more security-knowledgeable staff The ideal accompaniment to any new HP NonStop system.
Security Basics; The HP NonStop Server Architecture and Environment; Authentication:User Administration; Authentication, Granting Access to the HP NonStop Server; Authorization-Object Security; Gazette A to Z; Securing Applications. -- Appendeces: Gathering the Audit Information; HP NonStop File Codes: Third Party HP NonStop Server Security Vendors.
"XYPRO Technology Corporation"--Cover.
"TM" [trademark] appears after Nonstop in title.
Includes index.
Keywords: Client/server computing -- Security measures; Computer security; Hewlett-Packard computers -- Security measures; Electronic books